Standarization Of The Recipe For Randang Daging As Tradisional Food In Nagari Sungai Tanang - Deslia Khairani; Elida Elida (Universitas Negeri Padang, 2020)
This study aims to standardize the recipe for beef randang in Nagari Sungai Tanang, Banuhampu District, Agam Regency which includes ingredients, spices, tools, processing methods and quality analysis in terms of shape, color, aroma, texture and taste. The background of the research was the differences in the use of basic spices, cooking techniques and the dosage in randang processing, resulting in inconsistent and varied quality. This type of research is a mixed method, which is a combination of qualitative and quantitative research. Qualitative data sources were obtained from people who were experts in making randang and quantitative data sources were obtained from 9 trained panelists who knew about randang. Based on the research results, it was found that the standard recipe for meat randang includes the main ingredients, spices, tools, processing techniques and quality. The organoleptic test of the standard recipe for meat randang resulted in a less square shape, dark brown in color, fragrant, oily dry texture and savory taste.